2021
DOI: 10.2147/opth.s324245
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Vein Imaging: What Can It Tell Us?

Abstract: This review article summarizes the patho-anatomy of the vortex veins, the major drainage channels for the choroid, and describes the various pathways of diseases associated with vortex vein abnormalities. This report also details the technical advancements to image the vortex veins, such as ultra-widefield indocyanine green angiography, which are critical to elucidate the importance of the vortices in various retino-choroidal disorders. Future applications of these advanced imaging systems to better understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 82 publications
1
7
0
Order By: Relevance
“…Previous study proposed that the anastomoses in CSC occurred nearly uniformly among the superonasal, superotemporal, and inferotemporal vortex vein systems 10 , 13 , 14 . The relatively asymmetric distribution of choroidal thickness, choroidal volumes and large-choroidal vessel density found in our study may further support the view that the pathogenesis of typical CSC could involve congestion due to the impaired drainage of the affected vortex veins 1 , 8 , 10 , 14 16 , consistent with the result of Ishikura et al’s study 12 . In the study by Nishihara et al 17 , they found the choroidal thickness was significantly thicker in the eyes with CSC than that in the normal eyes at subfoveal choroidal thickness, at 5 mm superior, and at 7 mm superior from the fovea.…”
Section: Discussionsupporting
confidence: 92%
“…Previous study proposed that the anastomoses in CSC occurred nearly uniformly among the superonasal, superotemporal, and inferotemporal vortex vein systems 10 , 13 , 14 . The relatively asymmetric distribution of choroidal thickness, choroidal volumes and large-choroidal vessel density found in our study may further support the view that the pathogenesis of typical CSC could involve congestion due to the impaired drainage of the affected vortex veins 1 , 8 , 10 , 14 16 , consistent with the result of Ishikura et al’s study 12 . In the study by Nishihara et al 17 , they found the choroidal thickness was significantly thicker in the eyes with CSC than that in the normal eyes at subfoveal choroidal thickness, at 5 mm superior, and at 7 mm superior from the fovea.…”
Section: Discussionsupporting
confidence: 92%
“…Ischemia secondary to occlusion of the choriocapillaris triggers the development of CNV. Our theory of anastomosis is becoming a new trend in the understanding of pachychoroid diseases [ 34 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The vortex vessels, located in the middle layer of the eyeball wall, drain the choroid. They are difficult to detect by direct observation but can be observed more clearly with indocyanine green angiography (ICGA) than with other non-invasive techniques (6). However, research on vortex veins mostly transforms the ICGA image into binary image, and then manually segment the quadrants based on the position of the vortex vein to measure the brightness of each quadrant for research (7).…”
Section: Introductionmentioning
confidence: 99%